Treatment patterns, adverse events, and economic burden in a privately insured population of patients with chronic lymphocytic leukemia in the United States. (29th May 2019) - Kabadi, Shaum M.; Goyal, Ravi K.; Nagar, Saurabh P.; Kaye, James A.; Davis, Keith L.
Abstract: Introduction: Contemporary data describing treatment patterns, adverse events (AEs), and outcomes in patients with chronic lymphocytic leukemia (CLL) in clinical practice are lacking. We conducted a retrospective cohort study and assessed treatment patterns, AEs, health‐care resource use (HCRU), and costs in patients with diagnosis of CLL. Methods: Using a nationally representative population of privately insured patients in the US, adult patients with CLL diagnosis (July 2012‐June 2015) were selected if they had continuous health plan enrollment for ≥12 months before the first CLL diagnosis without any evidence of any CLL‐directed treatment. Treatment patterns up to four lines of therapy (LOT) and occurrence of AEs during CLL therapies were assessed. Mean per‐patient monthly HCRU and costs were assessed overall and by number of unique AEs. Results: Of all patients meeting the selection criteria (n = 7, 639; median age, 66 years), 18% (n = 1, 379) received a systemic therapy during study follow‐up. Of these, bendamustine/rituximab (BR) was the most common first observed regimen (28.1%), while ibrutinib was the most common therapy in the second (20.8%) and third (25.5%) observed regimens. The mean monthly all‐cause and CLL‐related costs, among patients treated with a systemic therapy, were 7, 943 (SD = 15, 757) and 5, 185 (SD = 9, 935), respectively. Mean monthly all‐cause costs increased by the number of AEs (from 905 [SD = 1, 865] among those with no AEs to 6, 032 [SD = 13, 290] among those with ≥6 AEs). Conclusions: Chemoimmunotherapy, particularly BR, was the most common first observed therapy for CLL, whereas ibrutinib was most preferred in the second and third observed lines of therapy during the study period. Findings demonstrate that the economic burden of AEs in CLL is substantial. Abstract : This population‐based cohort study describes recent real‐world evidence on treatment patterns, adverse events (AEs), health‐care resource use, and economic burden in a commercially enrolled population of patients with chronic lymphocytic leukemia (CLL) in the United States. Bendamustine‐rituximab was the most common first observed line of therapy, whereas ibrutinib was most preferred in the second and third observed lines during the study period (2012‐2016). This study shows that the AE burden associated with current treatments for CLL is substantial and suggests that the management of AEs may have a significant impact on overall health‐care costs.